Household Headship and Infant Mortality in India: Evaluating the Determinants and Differentials - Ashish Kumar Gupta, M Phil; Kakoli Borkotoky, M Phil; Amit Kumar, M Phi (International Journal of Maternal and Child Health and AIDS, 2014)
Background: There has been ample discussion on the levels and trends of infant mortality in India over time, but what remains less explored are the differentials in infant mortality according to household headship. This paper examined the differences in the determinants of infant mortality between male-headed households (MHH) and female-headed households (FHH).